Madzhab Tafsir Nusantara: Analisis Tafsir Al Quran Al Majid Al Nur Karya M. hasbi Ash-Shiddieqy - Iffatul Bayyinah (JIA (Jurnal Ilmu Agama), 2020)
When discussing the development of interpretations in Indonesia, there will be many figures included in it, including Muhammad Hasbi ash-Shiddiqie who is one of the Indonesian Muslim scholars who mastered many branches of Islamic knowledge including jurisprudence, hadith, and the Qur'an . This article describes M Hasbi Ash-Shiddieqy's thinking in interpreting the Qur'an. This study was analyzed descriptively and analytically by focusing on An-Nur's Tafsir al-Qur'anul Majid which was his interpretation. The interesting thing about this study is that the writer tries to uncover the interpretative schools in this interpretation, by looking at two aspects, namely internal and external. The internal aspects include methods and techniques of interpretation, while the external aspects cover Hasbi's life background including the social conditions of the Indonesian people which then greatly influence the model of interpretation, especially the verses related to the law. The results of this study indicate that the school of thought or style in this interpretation is a style of fiqhi. In interpreting the verses of the law Hasbi always try to present and explain the various opinions of the scholars or history that are in harmony with the verses interpreted, then relate it to the living conditions of the Indonesian people who are so pluralistic. He does not simply accept a law textually or in accordance with a particular school of fiqh, either Hanafi, Hambali, Maliki, or the school he has followed, namely the Shafi'i school.